Estetika Posmoderen: Idealisasi Seni Karawitan dalam Agama Hindu di Bali - Mawan, I Gede; Santosa, Hendra (Jayapangus Press, 2025)
Balinese musical art is essentially a cultural heritage passed down from generation to generation from the predecessors, and always adheres to existing traditions, relying on traditional patterns that develop in society. There is no traditional or religious ceremony in Bali without the involvement of musical arts. The diversity and complexity of Balinese gamelan playing has been the subject of study among researchers with various scientific approaches. This paper aims to discuss the art of Balinese gamelan music in the realm of postmodern aesthetic studies, one of the disciplines that is growing quite rapidly today. This research uses a descriptive method of analysis with data collection techniques such as observation, interviews, and literature studies as well as the author's experience as a musical performer. The results of this study show that in the last decade or 10 years there has been a fundamental change in the process of creating new works in Balinese karawitan. The process of creating new works, which has been based on a strong tradition, has now changed into contemporary (modern), postmodern or contemporary art. This phenomenon occurs due to the change in the mindset of artists who always want to keep up with the times. The forms or idioms of postmodern aesthetics found in the process of creating new works in Balinese musical art include Pastiche, Parody, Kitsch, Camp, and Schizophrenia. The emergence of postmodern aesthetic idioms in new Balinese musical works from artists at this time is to fulfill the need for beauty values as humans in general, also based on the desire to achieve intrinsic values contained in the art itself to achieve perfection as a human being.